A Drosophila melanogaster model shows that fast growing Metarhizium species are the deadliest despite eliciting a strong immune response - Jonathan B. Wang; Hsiao-Ling Lu; Huiyu Sheng; Raymond J St. Leger (Virulence)
We used Drosophila melanogaster to investigate how differences between Metarhizium species in growth rate and mechanisms of pathogenesis influence the outcome of infection. We found that the most rapid germinators and growers in vitro and on fly cuticle were the fastest killers, suggesting that pre-penetration competence is key to Metarhizium success. Virulent strains also induced the largest immune response, which did not depend on profuse growth within hosts as virulent toxin-producing strains only proliferated post-mortem while slow-killing strains that were specialized to other insects grew profusely pre-mortem. Metarhizium strains have apparently evolved resistance to widely distributed defenses such as the defensin Toll product drosomycin, but they were inhibited by Bomanins only found in Drosophila spp. Disrupting a gene (Dif), that mediates Toll immunity has little impact on the lethality of most Metarhizium strains (an exception being the early diverged M. frigidum and another insect pathogen Beauveria bassiana). However, disrupting the sensor of fungal proteases (Persephone) allowed rapid proliferation of strains within hosts (with the exception of M. album), and flies succumbed rapidly. Persephone also mediates gender differences in immune responses that determine whether male or female flies die sooner. We conclude that some strain differences in growth within hosts depend on immune-mediated interactions but intrinsic differences in pathogenic mechanisms are more important. Thus, Drosophila varies greatly in tolerance to different Metarhizium strains, in part because some of them produce toxins. Our results further develop D. melanogaster as a tractable model system for understanding insect-Metarhizium interactions.